SYK inhibition blocks proliferation and migration of glioma cells and modifies the tumor microenvironment. Issue 5 (1st February 2018) - Moncayo, Gerald; Grzmil, Michal; Smirnova, Tatiana; Zmarz, Pawel; Huber, Roland M; Hynx, Debby; Kohler, Hubertus; Wang, Yuhua; Hotz, Hans-Rudolf; Hynes, Nancy E; Keller, Georg; Frank, Stephan; et al.
Abstract: Background: Glioblastoma (GBM) is one of the most aggressive human brain tumors, with a median survival of 15–18 months. There is a desperate need to find novel therapeutic targets. Various receptor protein kinases have been identified as potential targets; however, response rates in clinical studies have been somewhat disappointing. Targeting the spleen tyrosine kinase (SYK), which acts downstream of a range of oncogenic receptors, may therefore show more promising results. Methods: Kinase expression of brain tumor samples including GBM and low-grade tumors were compared with normal brain and normal human astrocytes by microarray analysis. Furthermore, SYK, LYN, SLP76, and PLCG2 protein expressions were analyzed by immunohistochemistry, western blot, and immunofluorescence of additional GBM patient samples, murine glioma samples, and cell lines. SYK was then blocked chemically and genetically in vitro and in vivo in 2 different mouse models. Multiphoton intravital imaging and multicolor flow cytometry were performed in a syngeneic immunocompetent C57BL/6J mouse GL261 glioma model to study the effect of these inhibitors on the tumor microenvironment. Results: SYK, LYN, SLP76, and PLCG2 were found expressed in human and murine glioma samples and cell lines. SYK inhibition blocked proliferation, migration, and colony formation. Flow cytometric and multiphoton imaging imply that targeting SYK in vivo attenuated GBM tumor growth and invasiveness and reduced B and CD11b+ cell mobility and infiltration. Conclusions: Our data suggest that gliomas express a SYK signaling network important in glioma progression, inhibition of which results in reduced invasion with slower tumor progression.